Soil temperature record for the Bear Brook Watershed in Maine - Kaizad Patel; Sarah J Nelson; Cheryl J Spencer; Ivan J Fernandez (PANGAEA, 2018)
The Bear Brook Watershed in Maine (BBWM) is a long-term whole watershed manipulation experiment, established to study the effects of elevated nitrogen and sulfur deposition on ecosystem processes. Air and soil temperatures were recorded for the site from 2001 to 2016 using HOBO data loggers (Onset Computer Corporation). Temperature was recorded at four positions: (a) air, 100 cm above forest floor; (b) organic soil, 2-3 cm below the forest floor surface; (c) 10 cm below the interface of organic-mineral horizons, corresponding to the B horizon; and (d) 25 cm below the interface of organic-mineral horizons, corresponding to the B or BC horizon. Temperature was recorded every three hours. This dataset includes daily maximum, minimum, and mean temperatures, as well as monthly mean temperatures across the entire study period. Vegetation at the site was predominantly deciduous at low elevations and coniferous at high elevations, and we present data for both vegetation types.